Limit analysis of the undrained bearing capacity of offshore pipelines - Martin, C; White, D (2012)
The ultimate bearing capacity of a rigid, plane-strain pipe segment embedded in undrained clay is studied using numerical limit analysis. The pipe is considered to be 'wished in place' at invert penetrations ranging from zero to five pipe diameters, thus providing coverage of both on-bottom (partially embedded) and trenched (fully embedded) offshore pipelines. The soil is modelled as a rigid-plastic Tresca material with either uniform strength or strength proportional to depth. The effects of soil weight, interface roughness and interface tensile capacity are investigated in a systematic manner. All calculations are performed using the finite-element limit analysis code OxLim, which uses adaptive mesh refinement to compute tightly bracketed lower- and upper-bound plasticity solutions. The velocity fields from the upper-bound analyses provide the corresponding failure mechanisms. The paper initially focuses on purely vertical loading (penetration and uplift), and then addresses combined vertical and horizontal loading. A comprehensive set of design curves and failure envelopes is presented, with the results explained in terms of the changing failure mechanisms. These results are immediately applicable in practice. In particular, current industry-standard procedures for design against pipeline upheaval are critically reviewed, and are shown to have potentially unconservative shortcomings.